James Ensor - Maria Anna Cynkier (Groundings, 2017)
The article aims to outline the motifs present in works of James Ensor, a Belgian artist, whose art relates to the Symbolist approach to painting. By iconographical analysis combined with the examination of social factors, this article will evaluate Ensor’s contribution to the Symbolist practice during the end of the 19th century. Neglected for a long time by the discipline of art history, his flamboyant visions depicting masks and skeletons are now thought to constitute important emblems allowing for the exploration of the fin-de-siècle soul, troubled by progress and uncertainty and manifested in anarchism, degeneracy as well as spiritualism. This article will argue that the choice of iconography was not solely determined by the artist’s inner life, but its foundation can be found in the dramatic social changes occurring in the late 19th century Belgium and Europe.